Evaluation of the possibility of axial psoriatic arthritis patients meet classification criteria for axial spondyloarthritis and ankylosing spondylitis - E. E. Gubar; T. V. Korotaeva; Y. L. Korsakova; E. Yu. Loginova; A. V. Smirnov; A. V. Sukhinina; M. M. Urumova; S. I. Glukhova (Научно-практическая ревматология, 2023)
Objective – to analyze whether axial psoriatic arthritis (axPsA) patients meet classification criteria for axial spondyloarthritis (axSpA) and ankylosing spondylitis (AS).Subjects and methods. 104 patients (66 men and 38 women) with PsA according to CASPAR criteria were examined, all patients had back pain. Patients were evaluated for presence of inflammatory back pain (IBP) by ASAS criteria. Back pain not meeting the ASAS criteria was taken to be chronic back (chrBP). Patients underwent hands, feet and pelvis, cervical spine and lumbar spine X-rays. Erosions, osteolysis, and periarticular osteo-proliferative lesions were evaluated. Radiographically significant sacroiliitis (r-sSI) was defined as bilateral grade ≥2 or unilateral grade ≥3. 19 patients without r-sSI underwent sacroiliac joints MRI. 93 patients underwent HLA B27 examination. The number of patients who met the criteria for axSpA (ASAS) and the modified New York (mNY) criteria for AS was determined.Results. IBP was identified in 67 (64.4%), chrBP in 37 (35.6%) patients; 31 (29.8%) patients were of advanced age (over 40) at the onset of IBP/chrBP; 57 (58.8%) cases had r-sSI; 6 (31.6%) patients had MRI-SI; syndesmophytes were detected in 57 (58.8%) cases. Among 40 patients without r-sSI, 19 (47.5%) had syndesmophytes. In 38 (39.2%) out of 97 patients r-sSI was detected along with syndesmophytes, while 19 (19.6%) out of 97 patients had isolated r-sSI without spondylitis, and 19 (19.6%) out of 97 patients had isolated syndesmophytes without r-sSI. HLA B27 was present in 28 (30.1%) cases. 51 (55.4%) patients met criteria for axSpA. 41 (44.6%) patients didn’t meet criteria for axSpA, however 27 (65.9%) of them had syndesmophytes. 48 (48.5%) PsA patients met mNY criteria for AS.Among these patients a set of specific features was revealed: 18 (37.5%) had no IBP, 18 (37.5%) were of advanced age (over 40) at the onset of IBP/ chrBP, 34 (70.8%) had dactylitis, 38 (79.2%) – erosive polyarthritis, 23 (48.8%) – periarticular osteo-proliferative lesions, 14 (30.2%) – osteolysis, 23 (48,9%) – “chunky” non-marginal syndesmophytes, 40 (82,6%) – nail psoriasis, 28 (66,6%) patients were HLA-B27 negative.Conclusion. 45% of axPsA patients don’t meet criteria for axSpA. Characteristic features have been identified to differentiate axPsA from AS.